Reactive transport modeling of nutrients in arctic tundra streams - Kang, Woochul, author; Gooseff, Michael N., advisor; Ramirez, Jorge A., committee member; Bailey, Ryan, committee member; Covino, Tim, committee member (Colorado State University. Libraries, 2014)
The one dimensional solute transport inflow and storage (OTIS) model is used to simulate the transport of non-conservative and conservative solutes in arctic tundra streams. Field research was conducted in I8 Inlet and Outlet streams, (in northen Alaska) which are located upstream and downstream of 18 Lake between June and September 2010 and 2011 (thaw season) and these two streams are classified as alluvial, low gradient, headwater tundra streams. Repeat solute injections were conducted on both streams. Two sets of solute injections were made, Injection A is sodium chloride (NaCl) and phosphate (PO4) and Injection B is sodium chloride (NaCl) and ammonium (NH4). The sodium chloride is conservative and other two solutes are non-conservative solutes. With the observed concentration data, OTIS-P was used to estimate the model parameters values related to transport (dispersion and advection), transient storage and nutrient uptake mechanisms, by nonlinear least squares fit. The dispersion coefficient and main channel cross-sectional area parameters represented transport, storage zone cross-sectional area and exchange coefficient parameters represent transient storage, and 1st order decay coefficient in main channel and storage zone represent nutrient uptake. Additionally, transport and uptake metrics were calculated with estimated parameters. We assumed discharge, stream water temperature, and date (as a surrogate for thaw depth beneath the stream) were potential control variables on transport, transient storage, and nutrient uptake processes. Linear regression was conducted to identify potential relationships between these estimated parameters and metrics and control variables. Hydraulic controls are positively correlated with transport and transient storage mechanisms and stream temperature has positive relationships with nutrient uptake of non-conservative solutes (NH4 and PO4). Although, this study did not found direct influence of date (indicate of thaw depth) as a control, active layer condition is an important factor in solute transport dynamics in arctic region. Moreover, additional controls should be considered to explain solute transport dynamics more exactly. Beyond the scope of this study, for example, stream ecosystem status or activity may more directly explain NH4 and PO4 uptake variability.
Keywords: OTIS-P; OTIS; solute transport; transient storage; Arctic tundra stream